Communism in Eastern Europe - Rakowska-Harmstone, Teresa; Gyorgy, Andrew (Indiana University Press, 1979)
Communism in Eastern Europe is a comprehensive, lucid, and technically accurate general textbook in the field of East European politics organized around two types and patterns of approaches, namely, individual country-by-country case-studies, buttressed by certain significant functional chapters illuminating the key spanational and interregional problem areas of East Central Europe.